Práticas de música popular instrumental brasileira ao vibrafone: estudos e ferramentas para a performance solo com quatro baquetas - Natália Camargo Mitre de Oliveira (2019)
This research addresses performance aspects of instrumental Brazilian popular music repertoire (MPIB) on vibraphone. Different approaches are addressed to study the accompaniment of a solo vibraphone melody (harmonic, melodic and rhythmic). The approaches are investigated and worked on using tools that we have identified from different sources and that explore the idiomatic issues of the vibraphone with four mallets. In a case study of Gary Burton's performance of Chega de Saudade, the idiomatic characteristics of his performance were investigated, as well as possible studies for learning of this language with the four mallets vibraphone. Study-arrangements were elaborated to exemplify the use of each tool as well as arrangements that freely use the different elements studied throughout the research.